Thiazolothiazole‐Based Fluorescence Probe towards Detection of Copper and Iron Ions through Formation of Radical Cations. Issue 40 (25th October 2019) - Sathiyan, Govindasamy; Chatterjee, Shovon; Sen, Pratik; Garg, Ashish; Gupta, Raju Kumar; Singh, Anand
Abstract: This work describes the design and synthesis of fluorescent triphenylamine‐thiazolothiazole based donor‐acceptor‐donor chemosensor 4, 4′‐(thiazolo[5, 4‐ d ]thiazole‐2, 5‐diyl)bis( N, N ‐bis(4‐methoxyphenyl)aniline) (TTz‐1). TTz‐1 exhibited positive solvatochromism effect in the excited state due to its strong intramolecular charge transfer (ICT) properties. Potential application of TTz‐1 toward metal ion detection were explored systematically. It was established that the addition of Cu(ClO4 )2 . 6H2 O into TTz‐1 resulted in near‐infrared (NIR) colorimetric and fluorescent quenching allowing for Cu 2+ detection. EPR studies indicate that formation of radical cation occurs when Cu 2+ and TTz‐1 interact. TTz‐1 was also able to detect Fe 3+ employing a color change from orange to colourless (fluorescent). It was observed that the TTz‐1 emission peak at 567 nm was quenched after addition of Cu 2+ and Fe 3+ metal ions. Electrochemical analysis showed that LUMO values of the TTz‐1 decreased after addition of Fe 3+ and Cu 2+ . The limits of detection (LOD) for Cu 2+ and Fe 3+ detection by TTz‐1 were found to be 0.30 μM and 0.29 μM, respectively. These results suggest that the TTz‐1 is a highly selective and sensitive sensor for the detection of Cu 2+ or Fe 3+ ions. Abstract : Thiazolothiazole‐based donor‐acceptor‐donor (D−A‐D) fluorescent probe 4, 4′‐(thiazolo[5, 4‐ d ]thiazole‐2, 5‐diyl)bis( N, N ‐bis(4‐methoxyphenyl)aniline) (TTz‐1) was designed and synthesized for the selective recognition of Cu 2+ /Fe 3+ ions. TTz‐1 shows excellent fluorescence property with positive solvatochromism effect in the excited state. TTz‐1 with Cu 2+ ion leads to formation of radical cation resulting near‐infrared (NIR) colorimetric and fluorescent quenching.